Cathodal Transcranial Direct Current Stimulation Improves Focal Hand Dystonia in Musicians: A Two-Case Study - Marceglia, Sara; Mrakic-Sposta, Simona; Fumagalli, Manuela; Ferrucci, Roberta; Mameli, Francesca; Vergari, Maurizio; Barbieri, Sergio; Priori, Alberto (Frontiers in Neuroscience, 2017)
Focal hand dystonia (FHD) in musicians is a movement disorder causing abnormal movements and irregularities in playing. Since weak electrical currents applied to the brain induce persistent excitability changes in humans, cathodal tDCS was proposed as a possible non-invasive approach for modulating cortical excitability in patients with FHD. However, the optimal targets and modalities have still to be determined. In this pilot study, we delivered cathodal (2mA), anodal (2mA) and sham tDCS over the motor areas bilaterally for 20 minutes daily for five consecutive days in two musicians with FHD. After cathodal tDCS, both patients reported a sensation of general wellness and improved symptoms of FHD. In conclusion, our pilot results suggest that cathodal tDCS delivered bilaterally over M1 for 5 consecutive days may be effective in improving symptoms in FHD.